The Influence of Budget Planning on Optimizing the Use of Funds for Sport Day Activities in a Manufacturing Company in Karawang - Nurjaman, Raihani Salsabila Hasna; Isyanto, Puji (PT FORMOSA CENDEKIA GLOBAL, 2024)
Every company, whether service, trade or manufacturing, always strives to maximize profits by planning thoroughly and allocating budgets taking into account future conditions. Research conducted at a manufacturing company in Karawang aims to identify the influence of good budget planning on optimal use of funds. The method used is a quantitative approach, the data used in this research comes from primary data and secondary data. Data analysis using simple linear regression using SPSS software. The research results indicate that there is a positive influence between good budget planning and optimal use of funds. Therefore, realizing the budget well is important so that funds can be used optimally and avoid significant budget discrepancies.